2019
DOI: 10.1002/ardp.201800219
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes actively recognizing the glucose transporter GLUT1 and integrin αvβ3 for dual‐targeting of glioma

Abstract: The treatment of glioma is a great challenge because of the existence of the bloodbrain barrier (BBB). In order to develop an efficient glioma-targeting drug delivery system to greatly improve the brain permeability of anti-cancer drugs and target glioma, a novel glioma-targeted glucose-RGD (Glu-RGD) derivative was designed and synthesized as ligand for preparing liposomes to effectively deliver paclitaxel (PTX) to cross the BBB and target glioma. The liposomes were prepared and characterized for particle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Active targeting could be applied with conjugation of different targeting moieties (e.g., aptamers (X. Sun et al, ; Tang et al, ; X. Zhu et al, ), antibodies (Groysbeck et al, ; Sousa, Moura, Moreira, Martins, & Sarmento, ), peptides (Di et al, ; Fu et al, ), and several small molecules) on the surface of nanoparticles. The functionalized nanoparticles could bind to receptors expressed on GBM cells, including transferrin (Jhaveri, Luther, & Torchilin, ; Lakkadwala & Singh, ; X. Zhu et al, ), lactoferrin (J. Zhang et al, ), folic acid (M. Li et al, ), low‐density lipoprotein (Jiang, Zhang, Meng, & Zhong, ; Kim & Shin, ), and insulin receptor (Alibolandi, Charbgoo, Taghdisi, Abnous, & Ramezani, ).…”
Section: Nanotechnology‐based Therapy and Imaging For Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Active targeting could be applied with conjugation of different targeting moieties (e.g., aptamers (X. Sun et al, ; Tang et al, ; X. Zhu et al, ), antibodies (Groysbeck et al, ; Sousa, Moura, Moreira, Martins, & Sarmento, ), peptides (Di et al, ; Fu et al, ), and several small molecules) on the surface of nanoparticles. The functionalized nanoparticles could bind to receptors expressed on GBM cells, including transferrin (Jhaveri, Luther, & Torchilin, ; Lakkadwala & Singh, ; X. Zhu et al, ), lactoferrin (J. Zhang et al, ), folic acid (M. Li et al, ), low‐density lipoprotein (Jiang, Zhang, Meng, & Zhong, ; Kim & Shin, ), and insulin receptor (Alibolandi, Charbgoo, Taghdisi, Abnous, & Ramezani, ).…”
Section: Nanotechnology‐based Therapy and Imaging For Glioblastomamentioning
confidence: 99%
“…For dual targeting of the glucose transporter GLUT1 and integrin αvβ3 receptors in glioma, liposomes carrying paclitaxel were modified with glucose and arginylglycylaspartic acid (RGD) peptide. In integrin αvβ3-overexpressing tumor-bearing mice, the dual target liposome improved brain permeability and targeting and exhibited high accumulation at tumor sites (Fu et al, 2019).…”
Section: Lipid-based Nanosystemsmentioning
confidence: 99%
“…As one of the most effective transport systems, GLUT1 can effectively transport glucose through BBB to the brain. 76,77 Cancer cells frequently exhibit changes in glucose metabolism and an increased glucose demand. This leads to an overexpression of GLUTs in malignant tissues, especially GLUT1, which is related to the survival time of patients.…”
Section: 2mentioning
confidence: 99%
“…Published data from Böckenhoff and collaborators demonstrated that ApoE, in comparison to other BBB permeable therapeutic polypeptides including Angiopep (Ang-2), Apolipoprotein B (ApoB), and Transactivator of Transcription (TAT) exhibited the highest brain accumulation of the lysosomal enzyme Arylsulfatase A (ASA) ( 202 ). Studies by Fu et al demonstrated that incorporating a glucose-RGD derivative into paclitaxel containing liposomes for dual targeting [via GLUT1 (glucose) and integrin αvβ3 (RGD)] increased liposome accumulation in Kunming mice bearing C6 glioma tumors compared to paclitaxel alone ( 203 ).…”
Section: The Blood-brain Barrier Is the Critical Factor For The Successful Design Of Useful Drugs For Gbm Treatmentmentioning
confidence: 99%